Physical and Chemical Characteristic of Albizzia Sawdust as a Matrix in the Decomposition of Human Excreta Using Bio-toilet - Triastuti, Jovita; Sintawardani, Neni; Irie, Mitsuteru (Jurnal Ilmu dan Teknologi Kayu Tropis, 2008)
Bio-toilet (BT) is a dry closet that using sawdust as an artificial soil matrix due to the benefit characteristics of sawdust it self. In this study, Albizzia (Paraserianthes Falcataria) sawdust from a local sawmill was used as matrix in the decomposition of human waste in BT system. The study was carried out at Pesantren Daarut Tauhiid Bandung for about 4 months using BT type S-50 from Seiwa Denko Ltd, Japan. The human body waste from 25 students was loaded daily. Mixer was setting to run-on automatically with 15 minutes interval for 2 minutes; 1 minute to clockwise and counter-clockwise rotation respectively. Exhaust fan was operated continuously for aeration. Heater was run-off at first 2 months, and run-on at last 2 months. The physical and chemical properties of Albizzia sawdust, before (fresh) and after process (residual) were observed. Data showed that friction both among sawdust particles and between sawdust and screw material caused the particle size reduction due to the mechanical effect of mixing. Bulk density of sawdust increased (0.187 > 0.109 g/ml). Water retention increased from 2.09 to 2.55 ml/g. C/N ratio decreased significantly, from 200:1 to 27:1. Ash content of residual is higher than fresh sawdust (7.11 > 3.32%). The extractive compounds increased (3.68 > 1.8%). Lignin content tends increase, from 27.71 to 29.74% DM, meanwhile cellulose content decrease. Mineral P, K, and Na increased significantly during process. It was concluded Albizzia sawdust can be used as matrix in BT, but the residual should be replaced with fresh after 4 months usage due to maintain of BT performance. Residual sawdust has a good point as soil fertilizer due to its water retention, air capacity, and the high NPK content that would be valuable for plant.